Rozwijanie kompetencji interpersonalnych. Manual dla wykładowców opracowany przez Grupę Ekspercką działającą na Wydziale Filologicznym Uniwersytetu Wrocławskiego w ramach projektu finansowanego przez NCBiR (2014-2015) - Petryna, Sylwia; Kosicki, Janusz; Madej, Zenon; Czarnecka, Małgorzata; Drąg, Wojciech; Kuźnik, Anna; Kwieciński, Leszek; Wojciechowicz, Anna (2015)
Manual for lecturers about ways to develop interpersonal competences is a teaching material developed by an Expert Group established to create a platform for cooperation between employers and the Faculty of Letters of the University of Wrocław and to intensify the existing partnership between the university and business for the development of students' competences during the implementation of the project entitled “Programme for Improving the Competences of Students of Modern Languages at the University of Wrocław, Tailored to the Labour Market,” co-financed by the European Union as part of the European Social Fund, Human Capital Operational Programme, National Center for Research and Development (UDA-POKL.04.01.01-00-039/14-00; 01.10.2014-30.09.2015)
Keywords: employability of graduates of modern languages; entrepreneurship of graduates of modern languages; interpersonal competences; starting one’s own business; cooperation between universities and business; manual for lecturers